2016
DOI: 10.1038/srep27718
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the influence of TM6SF2 E167K variant on Plasma Concentration of Aminotransferases across different Populations and Diverse Liver Phenotypes

Abstract: A nonsynonymous E167K (rs58542926 C/T) variant in TM6SF2 gene was recently associated with nonalcoholic fatty liver disease (NAFLD). We explored the association between E167K and plasma concentrations of alanine (ALT) and aspartate (AST) aminotransferases through a meta-analysis. We also estimated the strength of the effect across diverse liver phenotypes, including NAFLD and chronic viral hepatitis; fourteen studies were included. We found that ALT (p = 3.2 × 10−6, n = 94,414) and AST (p = 0007, n = 93,809) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 41 publications
0
13
1
Order By: Relevance
“…These findings suggest that carriage of the TM6SF2 T risk allele is associated with decreased hepatic gene and protein expression, leading to a loss of function similar to the mutant PNPLA3 variant. In turn, the wild type TM6SF2 protein has been associated with increased serum VLDL levels and an elevated cardiovascular risk [32], but less liver injury [33]. Whether and how there may be cross-talk between TM6SF2 and signaling pathways pertinent for HCC development beyond mere intracellular lipid accumulation and lipotoxicity remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that carriage of the TM6SF2 T risk allele is associated with decreased hepatic gene and protein expression, leading to a loss of function similar to the mutant PNPLA3 variant. In turn, the wild type TM6SF2 protein has been associated with increased serum VLDL levels and an elevated cardiovascular risk [32], but less liver injury [33]. Whether and how there may be cross-talk between TM6SF2 and signaling pathways pertinent for HCC development beyond mere intracellular lipid accumulation and lipotoxicity remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients is increasing worldwide, accompanied by recent upward trends in obesity, westernized high-fat oral intake, gut dysbiosis, inadequate exercise, and comorbid metabolic disorders like diabetes mellitus (2,24). To identify factors associated with NAFLD, clinical studies have concluded that the prevalence, prognosis, and progression or severity of disease is significantly associated with SNPs in PNPLA3 (rs738409) and TM6SF2 (rs58542926) (4,5,11,25,26). Several studies have shown that the rs738409SNP in PNPLA3 causes a loss-of-function amino acid substitution (I148M) in PNPLA3 that affects regulation of lipid droplets in human hepatocytes and retinol metabolism in human HSCs, resulting in positive modulation of HSC activation (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…TM6SF2, of which rs58542926 C/T (E167K) was initially associated with liver fat accumulation and aminotransferase levels in a large GWAS study 21 and further replicated in subsequent studies, 21,[33][34][35] encodes for a protein involved in lipid metabolism. 12 Diverse areas of molecular knowledge gained on this gene/protein are presented in Figure 2.…”
Section: Precision Medicine and Large-scale Ge-nome And Exome Sequencmentioning
confidence: 92%